Glial and Neuronal Glutamate Transporters Differ in the Na+ Requirements for Activation of the Substrate-Independent Anion Conductance - Divito, Christopher B.; Borowski, Jenna E.; Glasgow, Nathan G.; Gonzalez-Suarez, Aneysis D.; Torres-Salazar, Delany; Johnson, Jon W.; Amara, Susan G. (Frontiers in Molecular Neuroscience, 2017)
Excitatory amino acid transporters are secondary active transporters of L-glutamate and L- or D-aspartate. These carriers also mediate a thermodynamically uncoupled anion conductance that is gated by Na+ and substrate binding. The activation of the anion channel by binding of Na+ alone, however, has only been demonstrated for mammalian EAAC1 (EAAT3) and EAAT4. To date, no difference has been observed for the substrate dependence of anion channel gating between the glial, EAAT1 and EAAT2, and the neuronal isoforms EAAT3, EAAT4, and EAAT5. Here we describe a difference in the Na+-dependence of anion channel gating between glial and neuronal isoforms. Chloride flux through transporters without glutamate binding has previously been described as substrate-independent or “leak” channel activity. Choline or N-methyl-D-glucamine replacement of external Na+ ions significantly reduced or abolished substrate-independent EAAT channel activity in EAAT3 and EAAT4 yet has no effect on EAAT1 or EAAT2. The interaction of Na+ with the neuronal carrier isoforms was concentration dependent, consistent with previous data. The presence of substrate and Na+-independent open states in the glial EAAT isoforms is a novel finding in the field of EAAT function. Our results reveal an important divergence in anion channel function between glial and neuronal glutamate transporters and highlight new potential roles for the EAAT-associated anion channel activity based on transporter expression and localization in the central nervous system.